Understanding motivations and future needs for data deposits at Korea Social Science Data Archive - Hyowon Kim; Do Won Kim; Jungwon Yang (IASSIST Quarterly)
Korea Social Science Data Archive (KOSSDA) has been integral in archiving and disseminating social science data in South Korea. As it transitioned into an independent research center under Seoul National University, we evaluated current data deposit process of KOSSDA through in-depth interviews with institutional data donors and identified future needs of data depositors. Motivations behind data deposit included recognizing data as a public good, addressing resource shortages in data curation, and enhancing data promotion. Future needs for KOSSDA included developing qualitative data guidelines, strengthening collaborations with donor institutions and academia as a whole, and automating the deposit process. These results guide the long-term strategy of KOSSDA to remain a leader in social science data archiving, ensuring its alignment with the evolving needs of the academic community.